(Nitrato-κO){N,N,N′,N′-tetrakis[(1H-benzimidazol-2-yl-κN3)methyl]cyclohexane-1,2-diamine}lead(II) hemiaqua{N,N,N′,N′-tetrakis[(1H-benzimidazol-2-yl-κN3)methyl]cyclohexane-1,2-diamine}lead(II) trinitrate dihydrate - Zuo-an Xiao; Ting-ting Jiang (Acta Crystallographica Section E, 2011)
In the title compound, [Pb(NO3)(C38H38N10)][Pb(C38H38N10)(H2O)0.5](NO3)3·2H2O, both PbII ions are coordinated in a distorted trigonal–prismatic environment by a hexadentate N,N,N′,N′-tetrakis[(1H-benzimidazol-2-yl)methyl]cyclohexane-1,2-diamine ligand. A nitrate and a half-occupancy water ligand form long coordination bonds to the PbII ions capping the trigonal–prismatic environment. In the crystal, the components are linked by N—H...O and O—H...O hydrogen bonds, forming a three-dimensional network. C—H...O interactions also occur.